Cryptococcus neoformans infection in a post-operative mastoid cavity of an immunocompetent individual: a rare case report - Gosavi, Rahul S.; Gupta, Akash D.; Gosavi, Shishir D.; Phatak, Jayanti U. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
This is a case report of isolated cryptococcosis in the operated mastoid cavity of an immunocompetent individual. A 24 year old immunocompetent male who underwent modified radical mastoidectomy presented to the OPD with complaints of otalgia and recurrent otorrhoea, not responding to regular medical line of treatment and aural toileting. Microscopy and culture of the ear dischrage revealed Cryptococcus neoformans. The patient was treated with oral and topical fluconazole and recovered completely. Although rare, cryptococcal mastoiditis should be considered even in an immunocompetent patient, as any delay in diagnosis and treatment can lead to fatal complications.